Simplifikasi Proses Transaksi Personalia pada Departemen HRD di PT. X - Katherin Natasya Tingkir (Jurnal Titra, 2016)
Acquisition of PT. X by parent company affect in human resource development (HRD) department which is changing personnel transaction process becomes complicated. There are 11 steps with the process time (lead time) per transaction for 31.93 days. The process will be simplified in order to proceed more effectively and efficiently with value stream mapping (VSM) method. The use of this VSM can determine which processes are value-added and non-value-added that can be further analyzed to see which process is waste. Hereafter, analyzing of the waste(s) and propose process simplification. Proposed of process simplification tested with simulations with some personnel transactions process. The results of the process simplification show a decrease processing time by 36.4% with the 7 steps and the lead time required for one transaction is 20.3 days. The procedures/ guideline (local content) need to be made due to personnel transaction process simplification which contains work steps. The local content will guide in processing the personnel transaction. Finally, overall changes need to be communicated using e-mail blast, presentation and easy card.